Functional Outcomes of Type V Acromioclavicular Injuries With Nonsurgical Treatment. Issue 10 (October 2016) - Dunphy, Taylor R.; Damodar, Dhanur; Heckmann, Nathanael D.; Sivasundaram, Lakshmanan; Omid, Reza; Hatch, George F.
Abstract : Introduction: This study investigated nonsurgical management of type V acromioclavicular (AC) injuries to determine functional outcomes and to attempt to identify factors associated with positive results. Methods: In a retrospective chart review, patients with radiographic and clinical evidence of type V AC injuries per the Rockwood classification were included in the study. Patients treated nonsurgically for ≥6 months were considered eligible for analysis. Functional outcomes were assessed using Disabilities of the Arm, Shoulder, and Hand (DASH) and American Shoulder and Elbow Surgeons (ASES) scores. Results: Twenty-two patients with a mean age of 42.2 ± 12.8 years were included in the study. The average coracoclavicular distance at the time of presentation was 26.3 mm (+199%). Mean DASH and ASES scores were 27.8 ± 17.7 and 62.8 ± 17.1, respectively, at an average of 34 months from the time of injury. Patients with normal DASH (⩽10) and ASES (>92) scores were younger than those with abnormal scores. At final assessment, 77% of the patients were currently working, with nine patients performing manual labor. Conclusion: Following nonsurgical management of type V AC injuries, most patients are able to return to work but have limited functional outcome scores. A small subset of patients with type V AC injuries can achieve normal functional outcomes with nonsurgical management. Level of Evidence: Level IV, Case Series Abstract : Supplemental Digital Content is Available in the Text.